FRBR Review Group initiatives and the world of linked data - Pat Riva (JLIS.it, 2013)
The FRBR Review Group has the mandate to review and maintain IFLA's family of conceptual models and to develop guidelines and interpretive documents to assist in the application of the models. In September 2011 the Aggregates Working Group submitted its final report, clarifying the modeling of three distinct types of aggregates within an FRBR framework. Since the approval of the FRSAD model in 2010, the FRBR Review Group has been concentrating its efforts on the development of a consolidated statement of the three models (FRBR, FRAD, FRSAD) in the entity-relationship formalism. The interrelationships between the models are particularly illuminating with regards to the subject entities and relationships and the "naming" entities. In parallel, the FRBR/CIDOC CRM Harmonisation Working Group has been working to extend FRBRoo to include the entities, attributes and relationships defined in FRAD and FRSAD. A third essential aspect of the FRBR Review Group's work is the development of a series of namespaces for the entities, relationships, attributes and user tasks as defined in the three models. This process has raised a number of interesting questions and often clarifies the underlying semantics of the models.